2015
DOI: 10.1155/2015/806042
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine May Repress the Weak LPS and Enhance the Strong Heat Shock Induction of Monocyte and Lymphocyte HSP72 Proteins but May Not Modulate the HSP72 mRNA in Patients with Sepsis or Trauma

Abstract: Objective. We assessed the lipopolysaccharide (LPS) or heat shock (HS) induction of heat shock protein-72 (HSP72) in peripheral blood mononuclear cells (PBMCs) of patients with severe sepsis (SS) or trauma-related systemic inflammatory response syndrome (SIRS), compared to healthy individuals (H); we also investigated any pre- or posttreatment modulating glutamine (Gln) effect. Methods. SS (11), SIRS (10), and H (19) PBMCs were incubated with 1 μg/mL LPS or 43°HS. Gln 10 mM was either added 1 h before or 1 h a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 64 publications
(69 reference statements)
1
16
0
2
Order By: Relevance
“…Although a negative correlation between hyperthermia and the number of receptors has been previously suggested [ 30 ], we could not find any relation between hGRα and temperature, lactate, glucose, LDH, IL-17, or PCT. In vitro, only heat shock induced mHSP72 and HSP72 mRNA but not lipopolysaccharide [ 31 ]. Our findings are in agreement with those of a recent study showing that in sepsis extracellular HSP72 and HSP90α are increased, while intracellular HSPs are repressed [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although a negative correlation between hyperthermia and the number of receptors has been previously suggested [ 30 ], we could not find any relation between hGRα and temperature, lactate, glucose, LDH, IL-17, or PCT. In vitro, only heat shock induced mHSP72 and HSP72 mRNA but not lipopolysaccharide [ 31 ]. Our findings are in agreement with those of a recent study showing that in sepsis extracellular HSP72 and HSP90α are increased, while intracellular HSPs are repressed [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, released GR is known to transcriptionally upregulate anti‐inflammatory cytokines and suppress pro‐inflammatory cytokines. It has been shown that both GR and HSPs are significantly elevated in the leucocytes of patients with severe sepsis …”
Section: Discussionmentioning
confidence: 99%
“…One notable example is the difference between animal and human studies regarding the protective effects of intracellular HSP72 against acute stress. Experimental studies have consistently shown a strong molecular, biological and clinical protective effect for HSP72 in sepsis, but clinical studies are inconclusive, varying from a protective in vitro effect to an in vivo HSP72‐mortality association …”
Section: Discussionmentioning
confidence: 99%
“…However, an ex vivo study showed that high-dose GLN did not induce Th1/Th2/Th17 cytokine responses in peripheral blood mononuclear cells (PBMC) obtained from patients with severe sepsis (18) . Also, GLN administration may repress heat shock protein 72 (HSP72) expression of PBMC after lipopolysaccharide exposure and enhance HSP72 proteins after heat shock induction in patients with sepsis (19) . The influence of GLN on T cell regulation and subsequent outcome in sepsis remain inconsistent.…”
mentioning
confidence: 99%